LIVING HADIS DALAM TRADISI RABU MALAM MAJELIS SELAWAT NARIYAH 4444 SEBAGAI SARANA BERTAWASUL - Danu Wibowo; Akhmad Jazuli Afandi (IAIN Kediri, 2021)
Abstract: The research studies the tradition of recitation nariyah 4444 blessings in Islamic boarding school Al-Jihad Surabaya. The focus is on knowing the signification of selawat nariyah and its relevance as a means of tawasul. It is based field research, that is, concerning living hadits phenomena characterized by descriptive, qualitative and inductive study. It means that the research aimed at gaining general picture or the description about living hadits. The approach to be used in the study is phenomenological one combined with functional theory. It results that the developing tradition in the life of Al-Jihad people is living-hadits one. In addition, there are some principal hadits to be used as guide in the activity. Besides, there is an important significance by the existence of the council, that is, spiritual aspect which cannot be losfrom people tradition.Keywords: Living Hadis, Tradition, Hadis, Nariyah Blessing, Tawasul